ANALISIS KEBUTUHAN KONSUMEN DALAM PENGEMBANGAN JENANG DENGAN METODE FUZZY QUALITY FUNCTION DEPLOYMENT (FQFD) [Analysis of Consumer Needs for Jenang Development with Fuzzy Quality Function Deployment (FQFD) Method] - Mas'ud Effendi; Luluk Mei Arifa; Siti Asmaul Mustaniroh (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2018)
UD. Bu Sulasmi is one of the business units that produce jenang in Blitar regency. The problem of the company was the marketing activity that has not been maximally indicated by the low sales of jenang which was 60% of the expected target. The low sales of jenang was due to competition with other jenang entrepreneurs. The purpose of this study was to determine the priority needs of consumers and improvements that need to be done by the company in increasing sales of jenang. The method used in this research was Fuzzy Quality Function Deployment (FQFD). The result of research indicated that attribute which become priority of consumer requirement were list of expiration date with a value of 0.0796, packaging design with a value of 0.0714, and accuracy of net weight of jenang with information contained in packaging with a value of 0.0665. Improvements that can be done by the company was to design a more attractive packaging design by including quality information on the packaging.